A novel gene arrangement among the Stylommatophora by the complete mitochondrial genome of the terrestrial slug Meghimatium bilineatum (Gastropoda, Arionoidea) - Xie, Guang-Long; Huang, Xiao-Chen (Molecular phylogenetics and evolution, 2019)
Stylommatophora is a main clade of Gastropoda that encompasses approximately 112 gastropod families and may exceed a total of 30,000 species. Twenty-four complete stylommatophoran mitogenomes have been sequenced to date, yet our understanding of mitochondrial evolution in stylommatophorans is still in its infancy. To further expand the set of available mitogenomes, we sequenced the mitogenome of Meghimatium bilineatum (Arionoidea: Philomycidae), a widespread land slug in East Asia. This is the first report on a mitogenome of the superfamily Arionoidea, and indeed on a terrestrial slug. The mitogenome of Meghimatium bilineatum comprises 13,972bp and exhibits a novel, highly distinctive gene arrangement among the Stylommatophora. Phylogenetic reconstructions based on the sequences of all protein-coding genes consistently recovered Meghimatium bilineatum as sister-group of the Succineidae. A phylogenetic reconstruction based on gene order, however, suggested a highly divergent tree topology, which is less credible when taking into account prior knowledge of stylommatophoran relationships. Our CREx (Common interval Rearrangement Explorer) analysis suggested that three successive events of tandem duplication random loss (TDRL) best explain the evolutionary process of gene order rearrangement in Meghimatium bilineatum from an ancestral stylommatophoran mitogenome. The present example offers new insights into the mechanisms of mitogenome rearrangements in gastropods at large and into the usefulness of mitogenomic gene order as a phylogenetic marker.
Gesehen am 17.06.2019